THE EFFECT OF PERSONAL SELLING AND MARKETING INFLUENCER ON THE PURCHASE DECISION OF MS GLOW FOR MEN PRODUCTS (STUDY ON UNIBA SURAKARTA STUDENTS) - Ilham S Dharmawan; Sudarwati Sudarwati; Fithri S Marwati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Purchasing decisions not only generate income for the company, but the more consumers who buy, the more the product is known to the general public. Companies can use Personal Selling and Influencer Marketing tactics to improve product sales so that consumers can acquire the things they manufacture. The purpose of this study is to examine the effect of personal selling and marketing influencers on purchase decisions. This study used a quantitative approach, using data derived from questionnaires delivered to students at the Islamic University of Batik (UNIBA) Surakarta utilizing the MS Glow For Men product. The Slovin formula was used to determine the sample size of 100 persons in this investigation. Purposive sampling is utilized, which means that the sample technique is determined by particular factors. The validity test, reliability test, multiple linear regression, and statistical test t test were employed in this study. The SPSS for Windows version 24 program was used for hypothesis testing. The results of data analysis show that (1) Personal Selling has a positive and significant influence on the Purchase Decision of MS Glow For Men products at the students of the Islamic University of Batik (UNIBA) Surakarta and (2) Marketing Influencers have a positive and significant influence on the Purchase Decision of MS Glow For Men products at the students of the Islamic University of Batik (UNIBA) Surakarta. The results of this study are expected to be used to improve marketing strategies by using personal selling and marketing influencers. . Keywords: Personal Selling, Marketing Influencer, Purchase Decision.